Improving Grade IV Students' Understanding of Changes in the States of Matter through Simple Experimental Methods. - Himmy Kanza Tsabita; Yuniar Tri Widyawati Zain; Fatihatur Rahmaniyah; Nurhayati; Agung Setyawan (Journal of Action Research in Education, 2026)
This research is motivated by the low understanding of students' concepts in science subjects, especially material on changes in the form of substances in grade IV UPTD SDN Keleyan 2. Initial conditions show that the average score of students' understanding of concepts is still low, which is 49.2. This is due to learning that is still dominated by lecture methods so that students are less active and less directly involved in the learning process. This research aims to improve students' understanding of concepts through the application of simple experimental methods. The type of research used is Class Action Research (PTK) with the Kemmis and McTaggart model which consists of two cycles, including planning, implementation, observation, and reflection. The subject of the study was 20 students in grade IV. Data collection techniques use observation, interviews, documentation, and tests. The results of the study show that the application of simple experimental methods can improve students' understanding of concepts. This is shown by the increase in the average score of students from 49.2 in the pre-cycle to 65 in the first cycle and increased again to 70.5 in the second cycle, as well as the increase in student activity in learning. Thus, the simple experimental method is effective in improving the understanding of the concept of IPAS in the matter of changing the form of substances.